689 Hybrid transvenous and surgical approach for the extraction of coronary sinus leads: a case series. (8th December 2021) - Ahmed, Ashraf; Arabia, Gianmarco; Bontempi, Luca; Cerini, Manuel; Salghetti, Francesca; Mitacchione, Gianfranco; Milidoni, Antonino; Stretti, Lorenzo; Bernardi, Nicola; Pezzola, Elisa; Cimino, Giuliana; Saccani, Nicola; et al.
Abstract: Aims: The rates of cardiac device-related infection have increased substantially over the past years. Transvenous lead extraction is the standard therapy for such cases. In some patients, however, the procedure cannot be completed through the transvenous route alone. A hybrid surgical and transvenous approach may provide the solution in such cases. Methods and results: We present three cases who underwent hybird transvenous and surgical extraction for coronary sinus leads due to infection of CRT-D systems. One patient had an Attain Starfix lead implanted in the coronary sinus. The procedures were performed under local anaesthesia with continuous haemodynamic and transthoracic echocardiographic monitoring. We highlight the characteristics of the patients, the features of the devices, the technical difficulties, and the outcomes of the procedures. In all cases, the right atrial and right ventricular leads were extracted through the transvenous route. In one patient, they were extracted using regular stylets and manual traction, while in the other two patients, telescoping dilator sheaths (Cook), Tightrail hand-powered mechanical sheaths (Spectranetics), and/or Glidelight Excimer Laser sheaths (Spectranetics) were used. The coronary sinus lead could not be retrieved due to extensive fibrosis after utilizing locking stylets and mechanical dilator sheaths in all three cases, in addition to rotational mechanical sheaths and laser sheaths in one case, so the patients were referred to surgery. Two patients underwent left mini-thoracotomy and one patient underwent midline sternotomy to extract the remaining CS lead. The target vein was identified and ligated, then the fibrosis around the lead was dissected, this was followed by lead retrieval through the surgical incision. The patient who underwent sternotomy suffered from mediastinitis, which required reoperation and mediastinal lavage. There were no complications in the other two patients. All three patients were reimplanted with a new CRT-D device on the contralateral side after the resolution of infection. Conclusions: A hybrid surgical and transvenous approach can be complementary in case the transvenous route alone fails to completely extract the coronary sinus lead. The transvenous approach can be used to free the proximal part of the lead, while the distal adhesions can be removed surgically, preferably though a limited thoracic incision.